2016
DOI: 10.1038/srep29747
|View full text |Cite
|
Sign up to set email alerts
|

High-quality III-nitride films on conductive, transparent (2̅01)-oriented β-Ga2O3 using a GaN buffer layer

Abstract: We demonstrate the high structural and optical properties of InxGa1−xN epilayers (0 ≤ x ≤ 23) grown on conductive and transparent (01)-oriented β-Ga2O3 substrates using a low-temperature GaN buffer layer rather than AlN buffer layer, which enhances the quality and stability of the crystals compared to those grown on (100)-oriented β-Ga2O3. Raman maps show that the 2″ wafer is relaxed and uniform. Transmission electron microscopy (TEM) reveals that the dislocation density reduces considerably (~4.8 × 107 cm−2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 51 publications
1
50
0
Order By: Relevance
“…XRD RC results indicated low threading dislocation density (TDD), dominated by screw and mixed type dislocations [13]. The TDD and the type of dislocations were confirmed by atomic force microscopy (AFM) and transmission electron microscopy (TEM) analysis (TDD was on the order of 108 cm 2 [13,14]). To the best of our knowledge, this is the best RC FWHM value for GaN obtained for materials grown on a Ga 2 O 3 substrate.…”
Section: Wafer Growthmentioning
confidence: 79%
See 4 more Smart Citations
“…XRD RC results indicated low threading dislocation density (TDD), dominated by screw and mixed type dislocations [13]. The TDD and the type of dislocations were confirmed by atomic force microscopy (AFM) and transmission electron microscopy (TEM) analysis (TDD was on the order of 108 cm 2 [13,14]). To the best of our knowledge, this is the best RC FWHM value for GaN obtained for materials grown on a Ga 2 O 3 substrate.…”
Section: Wafer Growthmentioning
confidence: 79%
“…The photoluminescence study reported in [13] has confirmed that the GaN on Ga 2 O 3 wafer has higher photoluminescence yield than GaN grown on Al 2 O 3 . AFM measurements have shown the root mean square (RMS) surface roughness as low as ∼ 0.3 nm over 400 µm 2 , and ∼ 0.17 nm over 25 µm 2 , indicating a significantly smoother surface compared to that of the commercial state-of the-art GaN grown on sapphire [13,14]. The XRD, TEM and AFM results indicated that the (−201) β − Ga 2 O 3 is the best orientation for GaN growth.…”
Section: Wafer Growthmentioning
confidence: 84%
See 3 more Smart Citations